Polydendrocytes display large lineage plasticity following focal cerebral ischemia - Honsa, Pavel; Pivonkova, Helena; Dzamba, David; Filipova, Marcela; Anderova, Miroslava (PloS one, 2012)
Polydendrocytes (also known as NG2 glial cells) constitute a fourth major glial cell type in the adult mammalian central nervous system (CNS) that is distinct from other cell types. Although much evidence suggests that these cells are multipotent in vitro, their differentiation potential in vivo under physiological or pathophysiological conditions is still controversial.To follow the fate of polydendrocytes after CNS pathology, permanent middle cerebral artery occlusion (MCAo), a commonly used model of focal cerebral ischemia, was carried out on adult NG2creBAC:ZEG double transgenic mice, in which enhanced green fluorescent protein (EGFP) is expressed in polydendrocytes and their progeny. The phenotype of the EGFP(+) cells was analyzed using immunohistochemistry and the patch-clamp technique 3, 7 and 14 days after MCAo. In sham-operated mice (control), EGFP(+) cells in the cortex expressed protein markers and displayed electrophysiological properties of polydendrocytes and oligodendrocytes. We did not detect any co-labeling of EGFP with neuronal, microglial or astroglial markers in this region, thus proving polydendrocyte unipotent differentiation potential under physiological conditions. Three days after MCAo the number of EGFP(+) cells in the gliotic tissue dramatically increased when compared to control animals, and these cells displayed properties of proliferating cells. However, in later phases after MCAo a large subpopulation of EGFP(+) cells expressed protein markers and electrophysiological properties of astrocytes that contribute to the formation of glial scar. Importantly, some EGFP(+) cells displayed membrane properties typical for neural precursor cells, and moreover these cells expressed doublecortin (DCX)--a marker of newly-derived neuronal cells. Taken together, our data indicate that polydendrocytes in the dorsal cortex display multipotent differentiation potential after focal ischemia.
Keywords: modely nemocí na zvířatech; Doublecortin Protein; Cell Proliferation; protein doublecortin; buněčná diferenciace; proteiny nervové tkáně; ischemie mozku; Animals; myši transgenní; zvířata; diferenciační antigeny; Disease Models, Animal; myši; neuroglie; proliferace buněk; Antigens, Differentiation; Neuroglia; Mice; Mice, Transgenic; Nerve Tissue Proteins; Cell Differentiation; Brain Ischemia